Effect of ethanolic extract from Piper sarmentosum on antihyperglycemic activity and complications in normal and streptozotocin-induced diabetic rats - Nittiya Suwannasom, Chutamas Thepmalee, Krissana Khoothiam, Chonthida Thephinlap (Journal of Applied Pharmaceutical Science, 2022)
The antihyperglycemic effect of ethanolic extract of Piper sarmentosum leaves (PSE) on diabetes and its complications was evaluated in streptozotocin-induced diabetic rats. Seventy-two Wistar albino rats (n = 72) were randomly distributed into six groups (n = 12 per group), namely control, normal PSE-treated, untreated diabetic, and PSE-treated diabetic groups. The normal PSE-treated and PSE-treated diabetic groups received 50 and 200 mg of PSE per kg of body weight (BW) daily for 60 days. The results demonstrate that the consumption of 50 and 200 mg PSE/kg BW significantly reduces the blood glucose level in diabetic rats after 60 days. The consumption of 50 and 200 mg PSE/kg BW also decreased the triglyceride and cholesterol levels in the diabetic group fed with PSE. However, the parameters of normal rats treated with PSE remained similar to those in normal control rats. Moreover, PSE decreased the levels of malondialdehyde, aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase, as well as blood urea nitrogen and creatinine. It also significantly increased the concentration of glutathione in both normal PSE-treated and PSE-treated diabetic groups. Thus, PSE has hypoglycemic, hypolipidemic, and antioxidant properties and can be used in the management of diabetes mellitus.
Keywords: Piper sarmentosum, diabetes, oxidative stress, streptozotocin, hyperglycemia